Pelatihan Perawatan Pompa Hidram untuk Kelompok Tani Utama Di Daerah Baumata - Wenseslaus Bunganaen; Muhamad Jafri; Verdy A Koehuan; Isak S Limbong; Yeremias M Pell; Kristomus Boimau (at-tamkin: Jurnal Pengabdian kepada Masyarakat, 2020)
Dry land agriculture is a crop cultivation activity carried out in moderate to severe drought conditions during most of the growing season. As a result, special cultivation techniques, types of crops and farming systems are needed to enable sustainable production. The partner involved in the Program Kemitraan Masyarakat (PKM) is a farmer group called the main farmer group. The main farmer group is located in Baumata village, Taebenu sub-district, Kupang district. This farmer group has used appropriate technology in the form of a hydram pump. The Hydram Pump, which is located in Baumata village is a product of the LP2M through the Mechanical Engineering Study Program, Faculty of Science and Engineering in 2018and is still running and is still being used by farmer groups. Based on the survey and coordination of the implementation team to the location until December 2019, it was concluded that there was a need for field activities in the context of training activities for members of farmer groups on how to repair, maintain and deal with pump problems which decrease productivity and aspects of pump work functions accordingly with a description of the report of the members of the Farmer Group.